A Rare Case of Cold Agglutinin Hemolytic Anemia Induced Gangrene - Daoud, Love; Shokry, Vivian; Daoud, Ehab (Journal of Medicine, 2015)
Gangrene is a rare and extreme presentation of cold agglutinin disease and our case is one of only few published reports in medical literature (less than twenty). In our patient severe hemolysis as manifested by elevated indirect bilirubin, LDH and low haptoglobin was triggered by unusual infectious organisms (E. Coli and Coagulase negative Staphylococcus). J MEDICINE July 2015; 16 (2) : 115-117